Komunikasi Pemasaran Berbasis Kearifan Lokal “Buah Maram” Dalam Membangun Brand Awareness pada Miring Varian Merona - Devy Sunny Putri Sofyanto; Denik Iswardani (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to analyze the local wisdom–based marketing communication strategy implemented by Brand Miring in building brand awareness through the Merona product variant. Brand Miring is a local herbal beverage that uses maram fruit as its main ingredient and promotes it as a symbol of peatland conservation and the preservation of local culture in West Kalimantan. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews with the brand team, resellers, and consumers, as well as documentation and observation of promotional activities. The results show that Brand Miring applies an Integrated Marketing Communication (IMC) strategy through various channels such as advertising, sales promotion, direct marketing, personal selling, public relations, and digital marketing, which are integrated with local cultural values. This strategy is effective in building brand awareness, particularly in terms of brand recognition and brand recall. The integration of local wisdom in marketing communication not only provides aesthetic value but also conveys educational and social messages, strengthening the brand’s position and differentiation in the beverage market.